22.2k views
2 votes
Assume the equation has a solution for z.
-cz+ 6z = tz + 83
z=?​

2 Answers

3 votes

Answer:

Explanation:

Assume the equation has a solution for z. -cz+ 6z = tz + 83 z=?​-example-1
User Kbunarjo
by
4.8k points
3 votes

Answer:

z = 83 / (- c + 6 - t)

Explanation:

Given:

-cz+ 6z = tz + 83

z=?​

-cz+ 6z = tz + 83

Collect like terms

-cz+ 6z - tz = 83

Factorize

z(- c + 6 - t) = 83

Divide both sides by (- c + 6 - t)

z(- c + 6 - t) / (- c + 6 - t) = 83 / (- c + 6 - t)

z = 83 / (- c + 6 - t)

User Pescolly
by
4.6k points